2021
DOI: 10.1001/amajethics.2021.394
|View full text |Cite
|
Sign up to set email alerts
|

Are Financial Incentives Appropriate Means of Encouraging Medication Adherence Among People Living With HIV?

Abstract: BACKGROUND: Financial incentives have been shown to improve antiretroviral (ARV) adherence for people living with HIV, but scholars have argued that this commodifies treatment and have debated the ethics of doing so. This article summarizes research on ethical processes and factors involved in an intervention that successfully improved ARV adherence among socially vulnerable people living with HIV. METHODS: Thirty qualitative interviews were conducted with intervention participants and field notes documenting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Ghose et al found a similar trend, and explain how patients repeatedly expressed being in favour of financial incentives as it helped them to pay for their food over and above maintaining them in HIV care. 37 Participants expressed an awareness of how financial incentives could assist them to fulfil their unmet needs. By contrast another South African study showed that both patients and providers generally did not link financial incentivisation with structural barriers to the HIV cascade like transport costs or food insecurity, but rather with individual factors like intrinsic motivation.…”
Section: Discussionmentioning
confidence: 99%
“…Ghose et al found a similar trend, and explain how patients repeatedly expressed being in favour of financial incentives as it helped them to pay for their food over and above maintaining them in HIV care. 37 Participants expressed an awareness of how financial incentives could assist them to fulfil their unmet needs. By contrast another South African study showed that both patients and providers generally did not link financial incentivisation with structural barriers to the HIV cascade like transport costs or food insecurity, but rather with individual factors like intrinsic motivation.…”
Section: Discussionmentioning
confidence: 99%